Analisis Tingkat Kepuasan Pelayanan Kepada Masyarakat pada Kantor Pertanahan Kabupaten Tana Toraja - Carolina Paulus Polli; Isak Pasulu; Jens Batara Marewa (CV. Ulil Albab Corp, 2024)
This study used a questionnaire distributed to the public who registered their certificates for the first time. Sampling using the Krecjie and Morgan sample table, namely 33 samples. The data analysis technique used was processing public satisfaction survey data using a weighted average value. From the test results, it is known that the index value in the Public Satisfaction Survey at the Tana Toraja Regency Land Office is 77.73, which indicates a B-level service quality and a good level of service unit performance. The results of the study shot that the public is satisfied with the services received